Analisis Efisiensi Produksi Menggunakan Metode Full Costing dan Break Even Point Pada Agroindustri Keripik Pisang Di Bandar Lampung: Studi Kasus: CV. Vanana Jaya Sinergi - Mega Rahma Sari; Bambang; Satria Putra Utama (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
This study aims to analyze the production efficiency of Melte Vanana banana chips agroindustry through the calculation of COGS using the full costing method, BEP analysis, and mapping the marketing structure applied by CV. Vanana Jaya Sinergi in Bandar Lampung City. The study was conducted in January 2025 using a mixed methods approach integrating quantitative and qualitative analysis. Data were collected through semi-structured interviews, participatory observation, and documentation involving eleven respondents directly engaged in the production and marketing chain. The sampling method applied was purposive sampling based on the respondents’ direct involvement in the production and marketing processes. Data validity was ensured through triangulation of sources and methods. The results showed that COGS per package varied across flavors: Vanilla Milk (IDR 4,696), Green Tea (IDR 5,014), Yummy Chocolate (IDR 5,656), Coffee Latte (IDR 5,788), and Cheese Melt (IDR 5,868), with a uniform selling price of IDR 10,000/unit, generating profit margins ranging from 41% to 53%. The overall Gross Profit Margin (GPM) reached 57.2%, exceeding the average of similar micro, small and medium enterprises. All product variants operated above the BEP with significant margins of safety. The marketing structure operated through three tiers distributors, agents, and resellers with a farmer share of 66.7%, indicating an efficient marketing channel. This study concludes that Melte Vanana agroindustry has achieved good production and marketing efficiency. A key limitation is the concentration of raw material supply (78%) on a single supplier, which poses a significant supply chain risk. Future research is recommended to incorporate BEP sensitivity analysis and broader multi-period data.